Arti Penting ASEAN Outlook on Indo Pacific bagi Visi Indonesia menjadi Poros Maritim Dunia - Artha Yudilla (Journal of Diplomacy and International Studies, 2021)
The geostrategic and geopolitical position provides opportunities for Indonesia not only as a global economicroute but also an international maritime security route. Maritime wealth is also a strength in Indonesia's maritime diplomacy in the international realm. This is then the basis for formulating mega-project policies to make Indonesia a global maritime axis. Since being declared in 2014, Indonesia has carried out a series of regional collaborations with the aim of achieving its vision as a Global Maritime axis. Among them are the Belt and Road Initiative with China to the IORA with countries in the Indian Ocean region. However, Indonesia's position as a Southeast Asian country with ASEAN as the first regional organization remains atop priority. It is proven that in 2019, Indonesia became the country that initiated the ASEAN Outlook on Indo Pacific with the aim of expanding the scope of cooperation among ASEAN countries. This also means that it will provide space for Indonesia to increase its power in the Indo Pacific region. This is certainly in line with Indonesia's vision to become the world's maritime axis. So this study will try to analyze the significance of the ASEAN Outlook on Indo Pacific (AOIP) for the vision of the World Maritime Axis.